Consequences of Supreme Court Decisions Upholding individual Constitutional Rights - Choper, Jesse H. (1984)
The thrust of this Article is to attempt to ascertain just what differences the Court's judgments upholding individual constitutional rights have made for those who fall within the ambit of their protection. It seeks to address such questions as: What were the conditions that existed before the Court's ruling? How many people were subject to the regime that was invalidated by the Justices? Was the Court's mandate successfully implemented? What were the consequences for those affected? At a subjective level, were the repercussions perceived as salutary by those (or at least most of those) who were the beneficiaries of the judicial decrees? At a more objective level - although the line between the subjective and objective on a matter like this is quite ethereal - were those effects understood by others as working to the advantage of the recipients, apart from their impact on society as a whole? Some of the case studies - and I use the term with trepidation - set forth below attempt to respond to most or all of these issues, while others (because of the nature of their subject) are more confined